Petrogenesis and tectonic implications of the late Paleoproterozoic (ca. 1.7 Ga) post-collisional magmatism in the southwestern Gyeonggi Massif at Garorim Bay, South Korea. Issue 5 (1st June 2021) - Kim, Ji-In; Choi, Sung Hi
Highlights: Ca. 1.7 Ga post-collisional granitic magmatism occurred in the SW Gyeonggi Massif. The ca. 1.7 Ga magmatism was overprinted by the Late Triassic crustal anatexis. They have negative εNd and εHf (t) values, indicating ancient crustal sources. The late Paleoproterozoic igneous activities are correlated to those of the NCC. Abstract: The Precambrian basement of the Gyeonggi Massif in the central Korean Peninsula consists mainly of Paleoproterozoic (2.0–1.8 Ga) gneisses. In this study, we present petrological, zircon U–Pb age and Hf isotope, and whole-rock geochemical and Sr–Nd–Pb isotope data for late Paleoproterozoic ( ca . 1.7 Ga) granitic gneisses and anatectic granites from the southwestern Gyeonggi Massif. Zircon U–Pb dating of two granitic gneisses and three anatectic granites yielded ages of 1685 ± 14, 1693 ± 8, 1683 ± 18, 1690 ± 6, and 1706 ± 17 Ma, respectively. The samples exhibit LILE enrichment, negative Nb–Ta anomalies, high Ga/Al ratios and HFSE contents, similar to A-type granites. Compared with typical anorogenic intra-continental rift-related granites (A1-type), Y/Nb and Ce/Nb ratios of the samples are much higher, and similar to those of post-collisional granites (A2-type). The εHf (t) values of late Paleoproterozoic zircons from the granitic gneisses and anatectic granites range from –17.8 to –7.0 and –15.3 to –9.7, respectively, indicating derivation from ancient crustal sources. The zircon U–Pb ages of the anatectic granites show that some of the late Paleoproterozoic intrusions underwent re-melting (i.e., anatexis) in the Late Triassic ( ca . 230 Ma). Whole-rock initial εNd (230 Ma) values of the anatectic granites (–29.4 to –28.1) and granitic gneisses (–26.3 to –24.3) are similar, indicating that the anatectic granites were sourced from the granitic gneisses. Late Paleoproterozoic igneous activity in the southwestern Gyeonggi Massif can be correlated with post-collisional activity in North China Craton, and was distinct from the coeval rift-related magmatism in South China Craton.